Upaya Guru dalam Meningkatkan Motivasi Belajar Siswa pada Masa New Normal - Siti Aisyah Has; syibran mulasi; masni masni (Atta'dib Jurnal Pendidikan Agama Islam, 2021)
This study aims to determine the efforts and obstacles found by the teachers at MAN 1 Aceh Barat in increasing students' learning motivation during the new normal period. This research is field research by using a qualitative approach with the data presented descriptively. The data collection techniques were carried out using interviews, observation and documentation to the selected respondents, namely Islamic Religious Education teachers at MAN 1 Aceh Barat. The results shows that the efforts made by teachers in order to increase the students’ learning motivation in the new normal including: instilling discipline and advising students about the importance of maintaining health and implementing health protocols, using e-digital media in the learning process, showing values in the form of numbers and symbols to students, providing an overview of the spirit of learning to the students, providing interesting materials in teaching, giving praise to students both in the form of verbal and objective praise, using interesting learning methods, having a good personality and providing good examples for students, carring out outdoor learning such as open places, libraries, prayer rooms, halls, and cottages, and encouraging students to take part in extracurricular activities, especially in the religious field. Meanwhile, the obstacles experienced by the teachers in the new normal period are: the students condition who are still carried away by the offline learning atmosphere, the emotional approach of students, the time of learning that coincide with prayer times, and there are some students who do not want to accept the teacher's opinion or advice. Keywords: Teachers’ Efforts in New normal Era, Increasing Learning Motivation, Learning in New Normal Era